FAKTOR-FAKTOR KRITERIA PEMILIHAN KONTRAKTOR YANG MEMPENGARUHI KINERJA PROYEK - Tamrin Sattung; Siti Haerani; Wardhani Hakim (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
Contractor selection is very important to ensure work can be done on time, on budget, and meet the quality. This study aims to analyze and understand in depth the factors of contractor selection criteria affecting project performance. The research was conducted at PT Vale Indonesia in Sorowako by taking samples of employees involved in the procurement of construction services. Data collection is done through documentation and questionnaire. Data analysis was done by factor analysis. The results show that there are three factors affecting project performance with a total cumulative variance of 61,708%. Factor I consist of conscientiousness, reputation, and cooperative relationship with eigenvalue of 3,693 and total variance of 39,930%. Factor II consists of job knowledge, job proficiency, initiative, and social skill with eigenvalue of 1,357 and total variance of 13,574%. Factor III consists of job experience, controllability, and commitment with eigenvalue of 1,120 and total variance of 11,204%. The findings of this study could be the reference of project owners in selecting contractors.